Infection Control Practices and Outcomes of Endoscopy Units in the Lombardy Region of Italy: A Survey From the Italian Society of Digestive Endoscopy During COVID-19 Spread. Issue 10 (November 2021) - Capurso, Gabriele; Archibugi, Livia; Vanella, Giuseppe; Testoni, Sabrina G.G.; Petrone, Maria C.; Fanti, Lorella; Greco, Salvatore; Cavenati, Sergio; Gaffuri, Nicola; Lella, Fausto; Pace, Fabio; Cengia, Gianpaolo; et al.
Abstract : Goals: The present survey from the Italian Society of Digestive Endoscopy (SIED—Società Italiana di Endoscopia Digestiva) was aimed at reporting infection control practice and outcomes at Digestive Endoscopy Units in a high-incidence area. Background: Lombardy was the Italian region with the highest coronavirus disease-2019 (COVID-19) prevalence, at the end of March 2020 accounting for 20% of all worldwide deaths. Joint Gastro-Intestinal societies released recommendations for Endoscopy Units to reduce the risk of the contagion. However, there are few data from high-prevalence areas on adherence to these recommendations and on their efficacy. Methods: A survey was designed by the Lombardy section of SIED to analyze (a) changes in activity and organization, (b) adherence to recommendations, (c) rate of health care professionals' (HCP) infection during the COVID-19 outbreak. Results: In total, 35/61 invited centers (57.4%) participated; most modified activities were according to recommendations and had filtering face piece 2/filtering face piece 3 and water-repellent gowns available, but few had negative-pressure rooms or provided telephonic follow-up; 15% of HCPs called in sick and 6% had confirmed COVID-19. There was a trend ( P =0.07) toward different confirmed COVID-19 rates among endoscopists (7.9%), nurses (6.6%), intermediate-care technicians (3.4%), and administrative personnel (2.2%). There was no correlation between the rate of sick HCPs and COVID-19 incidence in the provinces and personal protective equipment availability and use, whereas an inverse correlation with hospital volume was found. Conclusions: Adherence to recommendations was rather good, though a minority were able to follow all recommendations. Confirmed COVID-19 seemed higher among endoscopists and nurses, suggesting that activities in the endoscopy rooms are at considerable viral spread risk. Abstract : Supplemental Digital Content is available in the text.